A guinea pig model of Zika virus infection - Kumar, Mukesh (Virol J, 2017)
BACKGROUND: Animal models are critical to understand disease and to develop countermeasures for the ongoing epidemic of Zika virus (ZIKV). Here we report that immunocompetent guinea pigs are susceptible to infection by a contemporary American strain of ZIKV. METHODS: Dunkin-Hartley guinea pigs were inoculated with 10(6) plaque-forming units of ZIKV via subcutaneous route and clinical signs were observed. Viremia, viral load in the tissues, anti-ZIKV neutralizing antibody titer, and protein levels of multiple cytokine and chemokines were analyzed using qRT-PCR, plaque assay, plaque reduction neutralization test (PRNT) and multiplex immunoassay. RESULTS: Upon subcutaneous inoculation with PRVABC59 strain of ZIKV, guinea pigs demonstrated clinical signs of infection characterized by fever, lethargy, hunched back, ruffled fur, and decrease in mobility. ZIKV was detected in the whole blood and serum using qRT-PCR and plaque assay. Anti-ZIKV neutralizing antibody was detected in the infected animals using PRNT. ZIKV infection resulted in a dramatic increase in protein levels of multiple cytokines, chemokines and growth factors in the serum. ZIKV replication was observed in spleen and brain, with the highest viral load in the brain. This data demonstrate that after subcutaneous inoculation, the contemporary ZIKV strain is neurotropic in guinea pigs. CONCLUSION: The guinea pig model described here recapitulates various clinical features and viral kinetics observed in ZIKV-infected patients, and therefore may serve as a model to study ZIKV pathogenesis, including pregnancy outcomes and for evaluation of vaccines and therapeutics.